Prevalence of mental disorders among refugees: 25th European Psychiatric Association Congress materials short review - Frankova, Iryna (Psychosomatic Medicine and General Practice, 2017)
The European migrant crisis is one of the 21st century’s biggest challenges so far. Forced migration touches millions of peoples’ life. Some societies have sent many immigrants abroad, some have received or hosted, and still others have been in transit along paths of migration. Refugee mental health is a psychiatric challenge of the century. The demand for mental healthcare among people fleeing war and persecution can only grow further.